Synergistic Effect of Vaginal Trauma and Ovariectomy in a Murine Model of Stress Urinary Incontinence: Upregulation of Urethral Nitric Oxide Synthases and Estrogen Receptors - Chen, Huey-Yi; Chen, Wen-Chi; Lin, Yu-Ning; Chen, Yung-Hsiang (Mediators of Inflammation, 2014)
The molecular mechanisms underlying stress urinary incontinence (SUI) are unclear. We aimed to evaluate the molecular alterations in mice urethras following vaginal trauma and ovariectomy (OVX). Twenty-four virgin female mice were equally distributed into four groups: noninstrumented control; vaginal distension (VD) group; OVX group; and VD + OVX group. Changes in leak point pressures (LPPs), genital tract morphology, body weight gain, plasma 17β-estradiol level and expressions of neuronal nitric oxide synthase (nNOS), induced nitric oxide synthase (iNOS), and estrogen receptors (ERs—ERα and ERβ) were analyzed. Three weeks after VD, the four groups differed significantly in genital size and body weight gain. Compared with the control group, the plasma estradiol levels were significantly decreased in the OVX and VD + OVX groups, and LPPs were significantly decreased in all three groups. nNOS, iNOS, and ERα expressions in the urethra were significantly increased in the VD and VD + OVX groups, whereas ERβ expression was significantly increased only in the VD + OVX group. These results show that SUI following vaginal trauma and OVX involves urethral upregulations of nNOS, iNOS, and ERs, suggesting that NO- and ER-mediated signaling might play a role in the synergistic effect of birth trauma and OVX-related SUI pathogenesis.